The 2009–2010 step in atmospheric CO2 interhemispheric difference - R. J. Francey; J. S. Frederiksen (Biogeosciences, 2016)
The annual average CO2 difference between baseline data from Mauna Loa and the Southern Hemisphere increased by ∼  0.8 µmol mol−1 (0.8 ppm) between 2009 and 2010, a step unprecedented in over 50 years of reliable data. We find no evidence for coinciding, sufficiently large source and sink changes. A statistical anomaly is unlikely due to the highly systematic nature of the variation in observations. An explanation for the step, and the subsequent 5-year stability in this north–south difference, involves interhemispheric atmospheric exchange variation. The selected data describing this episode provide a critical test for studies that employ atmospheric transport models to interpret global carbon budgets and inform management of anthropogenic emissions.